Combined Ligand and Fragment‐based Drug Design of Selective Histone Deacetylase – 6 Inhibitors. Issue 5 (11th January 2019) - Ruzic, Dusan; Petkovic, Milos; Agbaba, Danica; Ganesan, A.; Nikolic, Katarina
Abstract: Histone deacetylase 6 (HDAC6) is unique hydrolase within HDAC family, having pleiotropic deacetylase activity against α‐tubulin, cortactin and dynein. Comprehensively, HDAC6 controls cell motility, apoptosis and protein folding, whereas alterations in its structure and function are related to the pathogenesis of cancer, neurodegeneration and inflammation. To define structural motifs which guide HDAC6 selectivity, we developed and compared three‐dimensional Quantitative Structure‐Activity Relationship ( 3D‐QSAR ) models for HDAC1 and HDAC6 inhibitors. The reduction of the bias in conformer generation was supported by virtual docking study by using crystal structures of human HDAC1 and HDAC6 isoforms. Following these findings, the combined ligand‐based and fragment‐based drug design methodologies were used in the design of selective HDAC6 inhibitors. Group of the most promising novel ligands was selected based on the predicted HDAC6 selectivity, pharmacokinetic profile, synthetic tractability, and in silico cytotoxicity against the wide range of human cancer cell lines. Abstract :